Effect of seepage on river bank stability - Dong, Bo (2011)
The experimental study, which is conducted in Hydraulics Modeling Laboratory, deals mainly with the riverbank stability. The study focuses on investigating riverbank stability under seepage effect and main flow in the channel. The riverbank was modeled in a 7-meter long flume with a test section of 1.1 meter. The test slope had a width-to-depth ratio of 2.5 and it was made up of cohesionless sand with grain size d50 = 0.2 mm.